Effect of enteral nutritional support on nutritional status of patients with gastric cancer receiving chemoradiotherapy after gastrectomy (Annals of Medical Research, 2021)
Aim: To evaluate the effects of enteral nutritional support in gastric cancer patients who received chemoradiotherapy (CRT) after gastrectomy.Materials and Methods: Patients who underwent total/subtotal gastrectomy due to gastric cancer and received postoperative CRT between January 1, 2010 and December 31, 2015 at Zonguldak Bülent Ecevit University Faculty of Medicine General Surgery Clinic were included in the study. The nutritional risk of patients was recorded using NRS-2002. The values of patients at the scheduled routine clinical follow-up at the end of the first year were compared with baseline values.Results: While 64.7% (n=22) of the patients continued to receive enteral nutritional support regularly (CNS group), 35.3% of the patients (n=12) discontinued nutritional support (DNS group). Patients in the DNS group had significantly lower baseline NRS-2002 scores (p=0.049). The NRS-2002 score of the CNS group decreased significantly at follow-up compared to the pre-CRT values. At the end of the first year, statistically significant increases were found in body weight, body mass index, transferrin level and vitamin D level of both patient groups. While the mean RBC count decreased significantly in the CNS group (p=0.002), there was no significant difference in the DNS group (p=0.382). When the amount of temporal change in RBC was evaluated, there was a significant difference between the DNS and CNS groups. Although vitamin B12 level and urea level increased in both groups, this increase was significant only in the DNS group (p = 0.049).Conclusions: In this study, it was determined that gastric cancer patients who continued enteral nutrition in the first year after CRT had significantly higher nutritional risk before CRT. Enteral nutrition reduces nutritional risk and shows positive results on nutritional parameters such as body weight, ferritin, transferrin, vitamin D, vitamin B12.